Analisa Unjuk Kerja Speaker pada Fasilitas Peralatan Carcall di Bandara Soekarno - Hatta - Al Ghani, Nur Rozaq; Wahyudi, Johan; Sudarta, Arafa (Politeknik Penerbangan Indonesia Curug, 2025)
Public Address System (PAS) and Carcall are supporting audio facilities at the airport. PAS is used inside the building to convey information to passengers, while Carcall is used in the outdoor area for communication with the vehicle fleet. The Carcall system consists of amplifiers and speakers with certain impedances. An imbalance between impedance and power capacity can reduce sound quality. To identify the root of the problem, the Root Cause Analysis and Fishbone Diagram methods are used. The application of the Pareto Diagram shows that 20% of technical problems related to impedance and power cause 80% of sound quality disturbances. Solving this problem can significantly improve the performance and durability of the Carcall device at Soekarno–Hatta Airport.